SAMPAH PLASTIK, LIMBAH PANGAN, DAN BIOPLASTIK - Oktavia Nurmawaty Sigiro; Asti Febrina; Shinta Marito Siregar; Purnama Nur Sakinah; Nuria; Ashani; Dea Apriani; Ega, (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
Plastic is a material that is used to help humans, but its waste, which is difficult to decompose, has become an unresolved problem to date. An alternative to controlling this problem is to reduce the use of synthetic plastics, including the use of bioplastics. Apart from plastic, some food waste is also an environmental problem, especially if the waste is in large quantities. This study aims to waste treatment from food waste such as coconut husk waste, rice husks, and pineapple leaves as bioplastics. This study used descriptive qualitative method. The results of the research show that coconut coir, rice husk and pineapple leaf waste can be used as material for the manufacture of bioplastics. The texture sequence of bioplastics from coarse to fine is bioplastics from rice husks, bioplastics from coconut husks, and bioplastics from pineapple leaf fibers. The color sequence of bioplastics made from types of waste ranging from brown to white, namely bioplastics from rice husk waste, pineapple fiber, and coconut coir.